The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.5007/1980-0037.2010v12n1p29
|View full text |Cite
|
Sign up to set email alerts
|

Diferença entre intensidade do exercício prescrita por meio do teste TCAR no solo arenoso e na grama DOI:10.5007/1980-0037.2010v12n1p29

Abstract: Resumo -A intensidade do treinamento pode ser influenciada pelo modo de exercício e tipo de terreno. Assim, os objetivos deste estudo foram: a) comparar os índices fisiológicos determinados no teste TCAR realizados no solo arenoso (SA) e no piso de grama natural (PGN) b) analisar as respostas de frequência cardíaca (FC) e lactato sanguíneo em exercício de carga constante em SA e PGN. Dez atletas de futebol (15,11±1,1 anos, 168±4,0cm, 60±4,0kg) foram submetidos ao teste TCAR para determinação do pico de velocid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
0
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
1
0
1
2
Order By: Relevance
“…On the other hand, PS T−CAR was, on average, 8.4% slower on SAND than on GRASS surface. These findings are similar to those reported by Cetolin et al (2010) who also demonstrated a lower PS T−CAR (−7.0%) at the end of the T-CAR performed on SAND compared with GRASS surface. Running on SAND is characterized by a lower horizontal take-off velocity and a subsequent shorter forward distance traveled during the flight phase of the stride, which directly implies a reduced stride length, especially in the highest running speeds (Pinnington et al, 2005;Alcaraz et al, 2011;Gaudino et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…On the other hand, PS T−CAR was, on average, 8.4% slower on SAND than on GRASS surface. These findings are similar to those reported by Cetolin et al (2010) who also demonstrated a lower PS T−CAR (−7.0%) at the end of the T-CAR performed on SAND compared with GRASS surface. Running on SAND is characterized by a lower horizontal take-off velocity and a subsequent shorter forward distance traveled during the flight phase of the stride, which directly implies a reduced stride length, especially in the highest running speeds (Pinnington et al, 2005;Alcaraz et al, 2011;Gaudino et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, previous research showed that SAND demanded significantly higher VO 2 and [La] values than running on GRASS at comparable speeds, thus resulting in a steeper slope in the VO 2 and [La] vs. running speed relationship (Pinnington and Dawson, 2001b). However, possible inferences regarding the energy contribution during the T-CAR should be interpreted with caution, since neither the present nor the previous study of Cetolin et al (2010) measured VO 2 responses during submaximal T-CAR speeds on SAND surface. Thus, future studies should further elucidate the extent to which these aforementioned aspects and other potential factors (e.g., peripheral fatigue) contribute to the slower PS T−CAR observed in SAND.…”
Section: Discussioncontrasting
confidence: 58%
“…Tal fato justifica-se pela precisão dos analisadores de gases nos valores de VO 2max , bem como aos diferentes ambientes em que os testes foram realizados. Os estudos de Cetolin et al 19 apontam que o mesmo teste aplicado em terrenos diferentes provoca diferentes solicitações metabólicas e exigências fisiológicas, acarretando assim em alterações nos resultados finais. Em seus trabalhos com o teste de TCAR realizado na grama e em solo arenoso, os autores perceberam que o pico de velocidade no solo arenoso é menor do que na grama, enquanto que a concentração de lactato [La] é maior na areia devido ao maior esforço físico para se deslocar em solos com menor resistência.…”
Section: Discussionunclassified
“…Contudo, quando imaginamos os gestos motores expressos em uma partida de futebol, a natureza dos testes realizados em laboratório se distancia daquilo que se observa em jogo (DRUST; REILLY; CABLE, 2000; DRUST; ATKINSON;REILLY, 2007). Diante disso, a utilização de testes de campo que se aproximam dessa realidade é de suma importância na determinação apropriada de tal índice(CASTAGNA et al, 2008;CETOLIN et al, 2010). Além disso, por mais que os testes laboratoriais possam apresentar grande validade interna e confiabilidade, eles necessitam de técnicos bem treinados para sua realização, bem como apresentam um alto custo operacional, o que inviabiliza, muitas vezes, sua aplicação(CASTAGNA et al, 2006b).…”
unclassified